It's the end when I say it's the end - Pastis, Stephan (Pastis, Stephan. Timmy Failure, 2019)
When his memoirs are being turned into a movie, Timmy must deal with a buffoonish movie director, while his polar bear business partner Total wants to be reunited with his family and Timmy's father is back in town working at a bar.